ER-Phagy and ER Stress Response (ERSR) in Plants - Zeng, Yonglun; Li, Baiying; Zhang, Wenxin; Jiang, Liwen (Frontiers in Plant Science, 2019)
The endoplasmic reticulum (ER) is the starting point for protein secretion and lipid biosynthesis in eukaryotes. ER homeostasis is precisely regulated by the unfolded protein response (UPR) to alleviate stress, involving both transcriptional and translational regulators. Autophagy is an intracellular self-eating process mediated by the double-membrane structure autophagosome for the degradation of cytosolic components and damaged organelles to regenerate nutrient supplies under nutrient deficient or stress conditions. A recent study has revealed that besides serving as membrane source for phagophore formation, the ER is also tightly regulated under stress conditions by a distinct type of autophagosome, namely ER-phagy. ER-phagy has been characterized with receptors clearly identified in mammal and yeast, yet relatively little is known about plant ER-phagy and its receptors. Here, we will summarise our current knowledge of ER-phagy in yeast and mammals, and highlight recent progress in plant ER-phagy studies, pointing towards a possible interplay between ER-phagy and ER-homeostasis under ER stress responses (ERSR) in plants.